TL1A/DR3 signaling deletion attenuates mucosal inflammation and alveolar bone loss in a murine model of spontaneous periodontitis - Sara Di Nicolantonio; Maria R. Miranda; Adrian Gomez-Nguyen; Davide Pietropaoli; Annalisa Monaco; Paola Menghini; Fabio Cominelli (Proceedings of the National Academy of Sciences, 2026)
TL1A and its receptor DR3 are key regulators of mucosal immune responses, but their role in periodontal disease is unknown. Herein, we investigated whether TL1A/DR3 signaling contributes to mucosal immune amplification and tissue-destructive inflammation in periodontitis using SAMP1/YitFc (SAMP) mice, which develop spontaneous ileitis and periodontal disease. DR3 deficiency markedly attenuated alveolar bone loss and improved periodontal architecture, restoring a phenotype comparable to healthy AKR (parental) controls. Gingival tissues from wild-type SAMP mice exhibited increased expression of both Tnfsf15 (encoding TL1A) and Tnfrsf25 (encoding DR3), with both positively correlating with disease severity. This was accompanied by elevated levels of IL-17, TNF-α, and IL-1β, and by increased numbers of CD4 + T helper cells and neutrophils. Conversely, SAMPxDR3 −/− mice exhibited reduced inflammatory cytokine production and immune cell accumulation. These findings support a model in which the TL1A/DR3 axis is associated with amplification of mucosal immune responses in periodontal disease, linking effector T cell activation, increased cytokine production, and recruitment of innate immune cells. Altogether, our data identify the TL1A/DR3 cytokine-receptor pair as a potential regulator of inflammatory circuits that drive periodontal pathology. Blocking this pathway may provide a therapeutic modality for patients affected by chronic periodontitis.